Diversity of Dragonfly Genus Drepanosticta in Tourism Forest Curug Cipendok, Banyumas District - Zaman, Mokhamad Nur; Fuadi, Bakhtiar Fahmi; Sultoni, Akhmad (Proceeding International Conference on Science and Engineering, 2019)
Cipendok especially have rich biodiversity. One of the themes is Javanese endemic dragonfly. Around 3 Javanese endemic dragonfly species was recorded in Curug Cipendok. Collection data was carried out in July until August 2017. The method used was exploration following path in several habitats, namely plantation, secondary forest, Pocung lake and field. Purpose of this study is to record the diversity of Javanese endemic dragonfly and distribution Drepanosticta in forest tourism curug Cipendok. The result from this observation is found three species that is Drepanosticta sundana, Drepanosticta gazella, and Drepanosticta spatulifera. The highest population is Drepanosticta gazella with 48% from totally individual and lowest is Drepanosticta sundana 13%. The diversity with Shannon-Wiener index is 0.97 that is low diversity. From observation distribution of Drepanostica only founded in a specific habitat, that is a secondary forest.